2017
DOI: 10.1016/j.aogh.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Active Case Finding of Tuberculosis: Randomized Evaluation of Simple and Infotainment Chest Camps

Abstract: Both types of chest camps are equally effective in active case finding of previously undiagnosed TB cases in rural areas in 2 provinces in Pakistan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…TB ACF in prisons may involve approaches such as mass screening, entry screening, routine screening, and exit screening. ACF of TB cases contributes to increasing TB case notification and treatment success rates and reducing mortality [22][23][24][25][26]. Hence, there is the need to sustain active search for TB cases in prisons, particularly in SSA where the burden of TB is still much higher compared to other regions in the world.…”
Section: Introductionmentioning
confidence: 99%
“…TB ACF in prisons may involve approaches such as mass screening, entry screening, routine screening, and exit screening. ACF of TB cases contributes to increasing TB case notification and treatment success rates and reducing mortality [22][23][24][25][26]. Hence, there is the need to sustain active search for TB cases in prisons, particularly in SSA where the burden of TB is still much higher compared to other regions in the world.…”
Section: Introductionmentioning
confidence: 99%
“…Community participation was increased by use of media for dissemination of messages [27,28], incentives and house to house visits [10]. The quality of screening was improved by training of volunteers, incentives for volunteers, symptom-checking with individual household members instead of head of the household improved the quality of screening [14].…”
Section: Good Practices In the Regionmentioning
confidence: 99%
“…On single outcomes by cascade, 11 (12.2%) studies reported TB testing outcomes[28][29][30][31][32][33][34][35][36][37][38], 22 (23.9%) reported TB diagnosis[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57], 15 (16.3%) reported on linkage to care[58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74], 21 (22.8%) studies reported treatment completion[11,12,[75][76]...…”
mentioning
confidence: 99%